Reservoir formation damage : fundamentals, modeling, assessment, and mitigation - Civan, Faruk (Gulf Professional Publishing, an imprint of Elsevier, 2023)
Reservoir Formation Damage: Fundamentals, Modeling, Assessment, and Mitigation, Fourth Edition gives engineers a structured layout to predict and improve productivity, providing strategies, recent developments and methods for more successful operations. Updated with many new chapters, including completion damage effects for fractured wells, flow assurance, and fluid damage effects, the book will help engineers better tackle today's assets. Additional new chapters include bacterial induced formation damage, new aspects of chemically induced formation damage, and new field application designs and cost assessments for measures and strategies. Additional procedures for unconventional reservoirs get the engineer up to date. Structured to progress through your career, Reservoir Formation Damage, Fourth Edition continues to deliver a trusted source for both petroleum and reservoir engineers.